Determinants of efficiency of Islamic banks: Indonesian evidence - Ahmad Fadlur, Rahman Bayuny; Haron, Razali (2016)
This study attempts to investigate the efficiency of Islamic banks in Indonesia and its determinants over the period of 2004-2014. Eleven full Islamic banks were selected for the sample. This study employs the Data Envelopment Analysis (DEA) in first stage of the analysis based on two inputs (fixed asset and deposits) and one output (financing income). Panel data regression is then employed in the second stage of analysis. This study finds that the efficiency scores of Islamic banks in Indonesia ranged from 61.4% to 96.4% between 2004-2014 with an overall efficiency of 75.6%. Regression analysis suggests that the efficiency of Islamic banks in Indonesia is negatively influenced by factors such as GDP growth, exchange rate and trade freedom while positively related with profitability, financing intensity, capitalization and non-financing expenses.